DEVELOPMENT AND ESTABLISHMENT OF A QUALITY-FRAMEWORK FOR THE LENA PROJECT. Issue 1 (14th December 2015) - Ciplea, Agnes M.; Kleine, Karl; Burckhardt, Björn B.; Läer, Stephanie; Breitkreutz, Jörg; Špatenková, Lucie; Klingmann, Ingrid
Abstract : Background: The LENA (Labeling of Enalapril from Neonates up to Adolescents) project has been initiated to improve the healthcare of children with heart failure by an enalapril orodispersible mini-tablet. The LENA consortium combines academic clinical research centers, SMEs (small and medium-sized enterprises) and a patient/parent advocacy organization. The objective of the project requires to comply with respective GxP regulations like Good Manufacturing Practice (GMP), Good Clinical (Laboratory) Practice (GCP/"GCLP"1) and Good Vigilance Practice (GVP). The project team is comprised of sub-teams experienced in paediatric clinical practice, medicines development, clinical research and project management, but not all team members work in an appropriate quality framework. Aim: To establish a well-documented, efficient quality system applying a new approach for ensuring quality in all trial aspects by combining existing organization-related quality system elements of the project partners with newly developed SOPs and overarching, integrating trial-specific elements to ensure a reliable quality environment for the LENA Phase I clinical trial. Methods: Based on the network-structure of the project organization, a strategy based on a team approach with joint responsibilities for the quality conduct of the project was pursuit, forming a QM Team consisting of the project leader, the leaders for pharmaceutical and clinical development and an external quality expert. The team compiled a quality manual and an organizational chart displaying the sub-teams and their responsibilities. Another responsibility of the team is the integration of existing SOPs and Work Instructions as well as the creation of procedures at the project level and furthermore the verification of appropriate qualification of all staff involved in the project through CVs, job descriptions and training records. Results: For the Phase I study, a thorough analysis of all existing relevant SOPs and Work Instructions, forms and other quality elements was performed, uncovered trial-related processes were identified and a work plan was established to fill the gaps with the smallest possible number of newly developed organization-related SOPs/Work Instructions and by preparing trial-specific process manuals. Demonstration of the trial team members was ensured by completing documentation concerning CVs, job description and training records. Among the sub-teams, the GCLP environment of the bioanalytical laboratory was started from scratch and could adequately support the LENA Phase I study by "GCLP" quality work and sample logistics. Conclusion: The consortiums approach enabled the preparation of a comprehensive, reliable GxP compliant quality system within a short timeframe and with the limited resources of a publicly funded project. 1 "GCLP" is used as acronym for a quality system established in compliance with "Reflection paper for laboratories that perform the analysis or evaluation of clinical trial samples" (EMA/INS/GCP/532137/2010; 28 February 2012) The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA).